Determination of nutrient availability in soil treated with agricultural chemical in cocoa plantation (R&D of Malaysian Cocoa Board Hilir Perak) / Nor'aqilah Mat Nawawi - Mat Nawawi, Nor'aqilah (Faculty of Plantation and Agrotechnology, 2016)
Economics of cocoa in Malaysia was declining from time to time. The government was recommending for applying chemical such as pesticide, herbicide and fertilizer is the best way to improve quality and quantity of yield in cocoa plantations. The accumulation of trace elements in the soil to restrict the sole function, cause toxicity to plants, and contaminate the food chain. Study aim is to investigate the correlation between the before and after applying the agricultural chemical use on soil. Plot of study is O.4 hectares situated at Research and Development Malaysian Cocoa Board Hilir Perak and top soil (0-25 cm) was taken as a sample. Analysis of soil sample was conducted by using Mehlich No. 1 as availability of nutrient uptake or extraction nutrient content. The result shows that, Al has a significant difference between before and after applying agricultural chemical with p-value ::;0.01. lron(Fe) and phosphorus (P) also shows that there is a significant difference in correlation in before applying agricultural chemical (p-value ::;0.01). The AI, Fe and P have their relationship between the three elements. Soil pH is one factor of the existing the element in the soil. High soil pH, will present high level of Al and Fe. But it can reduce the element P for plant uptake.